Vis-screen: easy and rapid identification of visual impairment - Abdul Mutalib, Othman; Naing, N.N.; Atif, Amin Baig; Asma', Hassan; Mohamad Rauf, Ayub; Siti Nor Aishah, . (2019)
Visual impairment and blindness is a global problem and one of the main agenda of World Health Organization program worldwide. Early detection and treatment are imperative for restoring normal vision. However, despite the ease of treatment, refractive errors and cataract remain the most common causes of visual impairment and blindness due to poor awareness and late detection. Early identification and presentation is important to improve eye care provision, in the effort to reduce visual impairment and blindness. Vis-Screen mobile application is developed for easy and rapid identification of visual impairment by any layperson. It is user-friendly and available in Google Play store for offline use by anyone, anywhere, and anytime in the community. The result is auto-generated according to WHO classification and can be shared to facilitate access with any vision and eye care providers available throughout the country.